2022
DOI: 10.1093/europace/euac092
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of occult atrial fibrillation in patients after cryptogenic stroke and transient ischaemic attack: PROACTIA

Abstract: Aims Studies with implantable cardiac monitors (ICMs) show that one-third of patients with cryptogenic stroke/transient ischaemic attack (TIA) have episodes of subclinical atrial fibrillation (SCAF) and benefit switching from antiplatelet- to anticoagulant therapy. However, ICMs are costly and resource demanding. We aimed to build a score based on participant’s baseline characteristics that could assess individual risk of SCAF. Methods and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Importantly, AF detection was based on ICMassisted diagnosis in 2 of them. 19,42 In our study, we were able to validate 4 AF-related risk scores: the CHA 2 DS 2 -VASc, HAVOC, Brown ESUS-AF, and C 2 HEST scores. The cutoff points and diagnostic metrics demonstrated in our study were similar to those previously reported.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Importantly, AF detection was based on ICMassisted diagnosis in 2 of them. 19,42 In our study, we were able to validate 4 AF-related risk scores: the CHA 2 DS 2 -VASc, HAVOC, Brown ESUS-AF, and C 2 HEST scores. The cutoff points and diagnostic metrics demonstrated in our study were similar to those previously reported.…”
Section: Discussionmentioning
confidence: 81%
“…36 Yet, those and other risk scores that were specifically developed among ischemic stroke cohorts, 20,[37][38][39][40] did not focus on patients with CS but evaluated patients with any kind of stroke. Finally, 4 risk scores 18,19,41,42 were constructed based on patients with CS and embolic stroke of undetermined source. Importantly, AF detection was based on ICMassisted diagnosis in 2 of them.…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective study, consecutive ESUS patients from the PROACTIA study 10 were referred to the Department of Cardiology, Akershus University Hospital, from 2016 to 2018. Patients above 18 years of age, hospitalized for the first time with non-disabling stroke or acute ischemic stroke syndrome (TIA), were screened according to the TOAST criteria 11 and ESUS criteria 2 by two neurologists and a cardiologist.…”
Section: Methodsmentioning
confidence: 99%
“…All study patients underwent neurovascular imaging by CT, MRI, or both to verify ESUS according to the TOAST and ESUS criteria, 3 , 11 as described previously. 10 …”
Section: Methodsmentioning
confidence: 99%
“…In the last years, several studies reported biomarkers associated with an increased risk of developing AF. These biomarkers include morphological cardiac features (atrial fibrosis, left atrial volume, 4 blood velocity in the left atrial appendage 5 ), electrocardiographic characteristics (P‐wave duration and morphology 6 ) and blood analytical determinations (NT‐proBNP, MR‐proANP 7,8 ). Evidence suggests that these biomarkers may actually be features of an atrial cardiopathy characterized by morphological and structural changes in the atria with associated remodeling that ultimately contributes to the development of AF 9 .…”
mentioning
confidence: 99%